Hospital accreditation in Mexico fails to improve the quality of healthcare: lessons from an impact evaluation - Gutiérrez, Juan Pablo; Rodriguez, Miguel Angel; Torres-Pereda, Pilar; Reyes-Morales, Hortensia (Frontiers in Public Health, 2024)
Healthcare quality in low-and middle-income countries poses a significant challenge, contributing to heightened mortality rates from treatable conditions. The accreditation of health facilities was part of the former health reform in Mexico, proposed as a mechanism to enhance healthcare quality. This study assesses the performance of hospital accreditation in Mexico, utilizing indicators of effectiveness, efficiency, and safety. Employing a longitudinal approach with controlled interrupted time series analysis (C-ITSA) and fixed effects panel analysis, administrative data from general hospitals in Mexico is scrutinized. Results reveal that hospital accreditation in Mexico fails to enhance healthcare quality and, disconcertingly, indicates deteriorating performance associated with increased hospital mortality. Amidst underfunded health services, the implemented accreditation model proves inadequately designed to uplift care quality. A fundamental redesign of the public hospital accreditation model is imperative, emphasizing incentives for structural enhancement and standardized processes. Addressing the critical challenge of improving care quality is urgent for Mexico's healthcare system, necessitating swift action to achieve effective access as a benchmark for universal healthcare coverage.